A descriptive study on the occurence of oral injuries among young soccer players - Lirag, Zenaida Pilar R.
The primary objective of this study was to investigate the occurrence of injuries to the teeth and its surrounding structures among young soccer players. A 1-paged questionnaire was distributed among 84 soccer players of the Makati and Alabang Football Schools. It was asked if they have sustained any oral injuries and the causes of the injuries, if they are aware of the use of the mouthguard, and the use or reason for non-use of the mouthguard. Of the 78 subjects, 56 (72%) responded that they have not been injured and 22 (28%) responded that they have been injured. The most frequently sustained injury was a cut lip (26.92%), followed by a bruised cheek (19.23%), bit lip (15.38%), chipped tooth (15.38%), loose tooth (7.69%), bruised lip (3.85%), cut chin (3.85%), cut tongue (3.85%), and lost tooth (3.85%). Falling down was the most common cause of oral injuries (41%), followed by bumping into another player (36%), then by being hit by the ball (23%). 26 (33%) of the 78 subjects reported that they knew about the existence of mouthguards, while the remaining 52 (67%) did not have any knowledge about it. 52 (53.61%) subjects cited "Didn't know that there is such a thing as a mouthguard" as the reason for the non-use of a mouthguard, followed by "Don't see the need for it" (34.02%) and "No one else wears mouthguards" (12.37%). The author concludes that (1) both soft and hard tissue oral injuries occur among young soccer players: (2) most injuries sustained were caused by falling down, bumping into another player and being hit by a ball: (3) there is a lack of awareness on the availability of protective mouthgears among young soccer players: (4) there are no measures taken to prevent injuries to the teeth and its surrounding structures among young soccer players.